The Expanded Clinic of the Dentistry course at UEM: a critical analysis based on the evaluation of records (Research, Society and Development, 2022)
The objective was to identify the contributions and challenges linked to the dynamics of an expanded clinic in the context of undergraduate teaching in Dentistry. 381 medical records were evaluated (2012-2016) and data were extracted regarding the demographic profile, completion of fields, main complaint, treatment plan options, number of discharges and referrals. There was a higher prevalence of adult, Caucasian and female patients. The professors' signature fields and treatment plan options were satisfactorily completed. There was a higher frequency of unsatisfactory completion of the medical record in cases in which treatment began on the same day of admission. The referral rate has increased over the years by 58%. Discharge rates were higher for patients who had three options for treatment plans and who spent less time in the OR. In 2015, the number of discharges and referrals was higher compared to other years, as well as the number of treatment plan options. In the years 2012 and 2015, the completion of CA records reached its best rates. It can be concluded that the Expanded Clinic, as a space for reception, planning, execution and management of multidisciplinary and multiprofessional treatments, requires periodic evaluations and reflections that support future actions and the application of pedagogical resources, involving all participants and segments, since that it is a process in constant evolution and improvement.